PERAN SIARAN ROHANI KATOLIK DALAM MEMBINA PAGUYUBAN KRISTIANI - Perdana, Romualdus Subyantoro Putra (P3TK, Sanata Dharma University, 2015)
This paper shows how the evangelization is important for the Church. Various efforts need to be developed to organize it in the middle of the world today. Social media is one tool that provides an opportunity for the Church to preach the faith to many people. Social media is a platform that allows the modern preaching the Gospel and Christian faith to be heard by more people. Sang Kristi broadcasting is one of the work of evangelization in the Archdiocese of Semarang who utilize social media, in this case is radio broadcasts. In the implementation, many challenges must be faced because of the changing trends in the use of media, because of the various media content (various things offered through the same medium) itself, and also because of the limited resources. FKK Sang Kristi meeting, off-air audiences activities, can complete what is lacking in the evangelization broadcasting method through Sang Kristi broadcasting. Things that cant be delivered through Sang Kristi broadcasting can be offered to the participants in this activity. The combination of these two activities would be able to realize an evangelization increasingly address the needs of the people as well as fulfilling the ideals of the Church